Empowering Students’ Global Communication Skills through English for Global Communication Workshop at Politeknik Bisnis Indonesia - Doris Yolanda Saragih; Erwin Sirait; Firinta Togatorop; Andi Setiadi Manalu; Poltak Pardamean Simarmata; Hengki Mangiring Parulian Simarmata (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program, entitled English for Global Communication: Strengthening Intercultural Competence among Polytechnic Students, was led by Doris Yolanda Saragih, S.Pd., M.Pd., in collaboration with Clementine and Josh, guest lecturers from the United Kingdom. The activity took place at Politeknik Bisnis Indonesia on September 1, 2025, involving 60 students across two interactive learning sessions. The program aimed to enhance students’ ability to communicate effectively in global settings by integrating language proficiency, cultural awareness, and practical communication strategies. The learning process applied a communicative and experiential approach, featuring discussions, simulations, and task-based learning to develop students’ speaking fluency, cross-cultural sensitivity, and confidence. The participation of native English speakers provided authentic exposure to international discourse and cultural perspectives, which enriched the overall learning experience. Evaluation results indicated a significant improvement in students’ oral communication skills, vocabulary use, and intercultural understanding. Furthermore, participants demonstrated higher motivation and readiness to apply English in academic and professional contexts. Overall, this community engagement initiative effectively contributed to enhancing global communication competence and supported the institution’s mission to cultivate globally competitive and culturally aware graduates.